Glucocorticoid Functional Reserve in Full-Spectrum Intensity of Primary Hypothyroidism - René Rodríguez-Gutiérrez; Camilo González-Velázquez; Gerardo González-Saldívar; Jesús Zacarías Villarreal-Pérez; José Gerardo González-González (International Journal of Endocrinology)
Adrenal function might be impaired in patients with primary hypothyroidism. The objective was to evaluate adrenocortical function using the low-dose cosyntropin test in patients with primary hypothyroidism. Consequently a prospective, longitudinal, controlled study of sixty adult patients with primary hypothyroidism was carried out. Patients naïve to L-T4 treatment were compared with control participants. A low-dose cosyntropin test was done before and after L-T4 therapy. Thirty and sixty minutes after the low-dose cosyntropin, the mean cortisol values were lower in the cases group (612.6 ± 133.1 and 603.4 ± 153.7 nmol/L) when compared to the control group (677.0 ± 82.4 and 669.9 ± 83.7 nmol/L) (P=0.001 and 0.003), respectively. After L-T4 therapy, this difference was lost. Four out of 60 cases (6.7%) taking a cortisol cutoff value of 500 mmol/L and 11 out of 60 (18.3%) having 550 mmol/L as the cutoff had adrenal insufficiency before L-T4 therapy. After L-T4 therapy, 50% and 81% of the cases had normal cortisol response. In conclusion, patients with different degrees of intensity of primary hypothyroidism had improved cortisol response after reaching euthyroidism. The incidence of adrenal insufficiency was 6.7–18.3% and more than 50% of the cases had a normal cortisol response after L-T4 therapy.